Biomass-derived binderless fibrous carbon electrodes for ultrafast energy storage. - Berenguer-Betrián, Raúl; García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Cazorla-Amorós, Diego; Morallón, Emilia; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Royal Society of Chemistry, 2015)
The possibility of storing energy efficiently and sustainably at little cost is crucial to prevent climate change and the exhaustion of natural resources. In this work we demonstrate that interconnected and porous carbon fibers easily obtained from lignin exhibit ultrafast charge–discharge and excellent energy density and cyclability performances, to be used as binderless and flexible electrodes in supercapacitors.
Keywords: Fibras de carbono; Electrodos de carbono; Lignina; Condensadores (Electricidad); Carbon fibers; Electrospinning; Supercapacitors; Lignin